2013
DOI: 10.3109/14764172.2013.807114
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a microwave device for treating axillary hyperhidrosis and osmidrosis in Asians: a preliminary study

Abstract: A microwave-based device has been developed to treat axillary hyperhidrosis by selectively heating the interface between the skin and underlying fat in the axilla. This study was conducted to evaluate the efficacy and safety of microwave-based devices for axillary hyperhidrosis and osmidrosis in Asians. Eleven patients (8 females and 3 males, age range 20-52 years, mean age 37.6 years) with axillary hyperhidrosis or osmidrosis were enrolled, treated with the microwave-based device, and followed up for 7 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…There is only one preliminary report evaluating the efficacy of microwave-based devices for axillary osmidrosis in Asians, which showed good efficacy (93.8%). 5 Our study further demonstrates good efficacy for axillary hyperhidrosis and osmidrosis. At the visits 30 days and 90 days after treatment series, 100% and 85.7%, respectively, of patients had achieved the primary end point of odor reduction.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…There is only one preliminary report evaluating the efficacy of microwave-based devices for axillary osmidrosis in Asians, which showed good efficacy (93.8%). 5 Our study further demonstrates good efficacy for axillary hyperhidrosis and osmidrosis. At the visits 30 days and 90 days after treatment series, 100% and 85.7%, respectively, of patients had achieved the primary end point of odor reduction.…”
Section: Discussionmentioning
confidence: 60%
“…4 However, treatment of axillary osmidrosis using this technique has only been reported in one preliminary study. 5 The objectives of this study were to investigate the efficacy, safety, and histological changes of microwave-based devices in treating axillary osmidrosis.…”
Section: Introductionmentioning
confidence: 99%
“…16 Improvement of axillary odor has been noted by patients. 18 Lee and colleagues reported using the microwave device on 11 Asian patients: 3 with HH only, 3 with HH and osmidrosis, and 5 with osmidrosis alone. The HDSS scores improved in all patients with HH (1-point to 3-point decrease in the HDSS) and axillary odor improved in all patient with osmidrosis.…”
Section: Curettagementioning
confidence: 98%
“…From the baseline HDSS assessment, 94% of patients experienced a 1-point decrease in their HDSS score, 16 and 55% to 83.3% experienced a 2-point or greater decrease in their HDSS score at 12 months after treatment. 16,18 Based on gravimetric assessments, 90% of patients experienced a 50% or greater reduction in axillary sweating, with an average reduction of 81.7%. 16 At 12 months after treatment, 85.5% of patients were satisfied with their treatment outcome.…”
Section: Curettagementioning
confidence: 99%
“…Studies that were found to use the HDSS tool were conducted globally, including the USA and Canada (n = 21 21,27,29,52,77,107,108,139,159,160,164,175,176,179,180,208,209,218,225,226,229 ), Spain (n = 6 167,207,210,224,230,231 ), the UK (n = 5 91,97,125,222,232 ), Germany (n = 5 2,131,145,161,227 ), Italy (n = 5 102,106, 136,214,223 ), France (n = 3 59,61,211 ), South Korea (n = 3 51,171,174 ), Australia (n = 2 53,221 ), Egypt (n = 2 213,219 ), Iran (n = 2 28,220 ), the Netherlands (n = 2 ...…”
Section: Hyperhidrosis Disease Severity Scalementioning
confidence: 99%